Penerapan Bisnis Berbasis Syariah pada Wirausaha Muslim - Nurwakhidah, Ana (Program Studi Ekonomi Syariah (ES) STAI Nahdlatul Ulama (STAINU) Malang, 2025)
In an effort to meet their daily needs, many Muslim entrepreneurs choose to become independent entrepreneurs. However, not all traditional business owners apply Sharia principles in their business activities. Understanding how Muslim entrepreneurs conduct businesses based on Islamic values ​​is crucial to fostering economic practices that are not only financially profitable but also morally and spiritually sound. This study aims to explore how the principles of honesty (shiddiq), trustworthiness (amanah), justice, and ihsan (good deeds) are applied in daily business practices at Bu Indah Plastic Shop, Bakroto Market, Ampelgading District, Malang Regency. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews, non-participatory observation, and documentation, and analyzed thematically through data reduction, presentation, and verification. The results indicate that this shop consistently applies Sharia principles through price transparency, trustworthy stock management, fair treatment of customers, and humanistic and empathetic service. These findings demonstrate that small-scale traditional businesses are capable of implementing Islamic economic principles sustainably. The implication is that other micro business can use this model as an example to strengthen business ethics and social contributions in daily economic activities.